Pacific Missionary George Brown 1835-1917 Wesleyan Methodist Church - Reeson, Margaret (ANU Press, 2013)
George Brown (1835-1917) was many things during his long life; leader in the Wesleyan Methodist Church in Australasia, explorer, linguist, political activist, apologist for the missionary enterprise, amateur anthropologist, writer, constant traveller, collector of artefacts, photographer and stirrer. He saw himself, at heart, as a missionary. The islands of the Pacific Ocean were the scene of his endeavours, with extended periods lived in Samoa and the New Britain region of today's Papua New Guinea, followed by repeated visits to Tonga, Fiji, the Milne Bay region of Papua New Guinea and the Solomon Islands. It could be argued that while he was a missionary in the Pacific region he was not a pacific missionary. Brown gained unwanted notoriety for involvement in a violent confrontation at one point in his career, and live+Y3d through conflict in many contexts but he also frequently worked as a peace maker. Policies he helped shape on issues such as church union, indigenous leadership, representation by lay people and a wider role for women continue to influence Uniting Church in Australia and churches in the Pacific region. His name is still remembered with honour in several parts of the Pacific. Brown's marriage to Sarah Lydia Wallis, daughter of pioneer missionaries to New Zealand, was long and rich. Each strengthened the other and they stand side by side in this account.